Ecotheology Menurut Seyyed Hossein Nasr dan Sallie McFague - Yustinus Andi Muda (Jurnal Teologi (Journal of Theology), 2020)
The universe as our shared home becomes the place and source of life for all creation. However, today's earth inhabited by humans is being hit by a global environmental crisis. To respond to the crisis, there has now emerged a new awareness in overcoming the ecological crisis, especially by exploring religious principles, which is called ecotheology, namely the study of the relationship between all beings living in their environment and God as their Creator. Related to this, there are two theologians from the Islamic and Christian religious traditions who talk about ecotheology. In his idea of ecotheology, Seyyed Hossein Nasr wants to remind people that nature is a representation of the presence of God in the world (wajh Allah) and humans as means of manifestation of Allah's will on earth (khalifatullah fi al-ardi) is one cosmic entity which cannot be separated from one another. Meanwhile, Sallie McFague wants to remind humans as partners of God to always realize that this universe is the body of God that needs to be respected and cared for as a form of responsibility for our shared home. So, the study of ecology as a paradigm always stems from reflection on human behavior, especially about the reflection of the relationship between humans and nature as their environment. Finally, a contextualized reading of McFagues ecotheology will be presented.